2021
DOI: 10.1145/3391297
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Defogging Image Recognition Algorithm Based on Bilateral Hybrid Filtering

Abstract: With the rapid advancement of video and image processing technologies in Internet-of-Things (IoT), it is urgent to address the issues in real-time performance, clarity and reliability of image recognition technique for monitoring system in foggy weather. In this work, a fast defogging image recognition algorithm is proposed based on bilateral hybrid filtering. Firstly, the mathematical model based on bilateral hybrid filtering is established. The dark channel is used for filtering and denoising the defogging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…As shown in Figure 2, we can see the relationship between IoT/sensor network and sentiment analysis. We have also found that with the development of the blockchain which is a pioneer cryptocurrency [15,[19][20][21][22], media and public opinions show increased usage of text analysis [23,24]. Blockchain is considered to be an innovative technology with epoch-making significance in recent years.…”
Section: Introductionmentioning
confidence: 73%
“…As shown in Figure 2, we can see the relationship between IoT/sensor network and sentiment analysis. We have also found that with the development of the blockchain which is a pioneer cryptocurrency [15,[19][20][21][22], media and public opinions show increased usage of text analysis [23,24]. Blockchain is considered to be an innovative technology with epoch-making significance in recent years.…”
Section: Introductionmentioning
confidence: 73%
“…In 2012, deep learning technology shined in the image classification competition and a research boom is set off in academia and industry. Since then, the research in the field of image has become hot, and it also promotes the research in the field of intrusion detection [25][26][27]. Zhang et al [28] proposed an anomaly network traffic detection method based on deep-level network and raw traffic data providing a detailed raw data processing process.…”
Section: Methods Based On Deep Learning In 2006 Professormentioning
confidence: 99%
“…The IoT system connects the Internet and information-sensing equipment to achieve intelligent control and management of all objects. It can be divided into three layers: Perception Layer [40], Network Layer, and Application Layer. Perceptual Layer is responsible for object collection and data processing.…”
Section: Level Dbmentioning
confidence: 99%